2009
DOI: 10.1002/bdra.20556
|View full text |Cite
|
Sign up to set email alerts
|

An association study of 45 folate‐related genes in spina bifida: Involvement of cubilin (CUBN) and tRNA aspartic acid methyltransferase 1 (TRDMT1)

Abstract: Our study indicates interesting new candidate genes and functional pathways for further study and confirms earlier findings. None of the genes CUBN, TRDMT1, ALDH1L1, or SARDH have been investigated previously for association with spina bifida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 32 publications
1
67
3
Order By: Relevance
“…Furthermore, mutations in RNA modification enzymes have also been shown to cause developmental defects, such as Hutchinson-Gilford progeria syndrome (NAT10) (Larrieu et al 2014), and primordial dwarfism (WDR4) (Shaheen et al 2015). In addition, mutations in RNA modification enzymes can cause the spinal cord to expose outside the body like spina bifida (TRDMT1) (Franke et al 2009) and infant death (EMG1) (Armistead et al 2009). …”
Section: Genetic Defectsmentioning
confidence: 99%
“…Furthermore, mutations in RNA modification enzymes have also been shown to cause developmental defects, such as Hutchinson-Gilford progeria syndrome (NAT10) (Larrieu et al 2014), and primordial dwarfism (WDR4) (Shaheen et al 2015). In addition, mutations in RNA modification enzymes can cause the spinal cord to expose outside the body like spina bifida (TRDMT1) (Franke et al 2009) and infant death (EMG1) (Armistead et al 2009). …”
Section: Genetic Defectsmentioning
confidence: 99%
“…Other candidate SNPs in the megalin gene, LRP2, were selected based on one previous study that evaluated megalin in relation to prostate cancer; four LRP2 SNPs showed some associations with prostate cancer risk (rs831003, rs2239598, 2268373, rs3944004) (28). We also included one SNP (rs1907362) in the CUBN gene that has been shown to have some functional importance in another pathway (29). Genotyping was conducted at the University Health Network's Analytical Genetics Technology Centre using the MassARRAY iPLEX Gold Sequenom Platform.…”
Section: Response Rate and Sample Sizementioning
confidence: 99%
“…Defects in cubilin, a proximal tubular membrane protein, have been associated with both megaloblastic anemia and tubular proteinuria [11][12][13][14]. Cubilin also acts to reabsorb the majority of filtered albumin from the urine and recently, genome-wide association studies have identified SNPs in CUBN in association with albuminuria [15] and B 12 levels [16,17].…”
Section: Discussionmentioning
confidence: 99%